2003
DOI: 10.1159/000068712
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Gene Polymorphism, Hypercholesterolemia and Glomerular Filtration Rate in Type 2 Diabetic Subjects: A 9-Year Follow-Up Study

Abstract: Objective: To study the association between apolipoprotein E (apoE) genotype and the rate of decline in glomerular filtration rate (GFR) in type 2 diabetic patients in a 9-year prospective study. Methods: GFR was determined in 84 type 2 diabetic patients by plasma clearance of 51Cr-EDTA at baseline and after 9 years of follow-up. ApoE genotypes were determined by polymerase chain reaction and restriction enzyme HhaI digestion and designated as Ε4 allele group (apoE4/2, 4/3 and 4/4 genotypes; n = 20)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…51 APOE also exerts a major role in the pathogenesis and the progression of a variety of renal diseases, as well as in the atherosclerotic complications associated with them. Some studies have provided evidence that the APOE ∊4 allele is a risk factor for the progression of renal failure, 52 whereas others have shown that APOE ∊2 allele carries a genetic risk for renal complications. 53,54 Liberopoulos et al 55 reported that the APOE ∊2 allele is independently associated with increased serum uric acid levels in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…51 APOE also exerts a major role in the pathogenesis and the progression of a variety of renal diseases, as well as in the atherosclerotic complications associated with them. Some studies have provided evidence that the APOE ∊4 allele is a risk factor for the progression of renal failure, 52 whereas others have shown that APOE ∊2 allele carries a genetic risk for renal complications. 53,54 Liberopoulos et al 55 reported that the APOE ∊2 allele is independently associated with increased serum uric acid levels in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%